Tranformasi Program Eco-Pesantren Sebagai Inovasi Pendidikan Islam Berwawasan Lingkungan - Karya Bakti, Imam; Rohman, Miftakhul (SINDA: Comprehensive Journal of Islamic Social Studies, 2024)
Environmental damage is a very urgent phenomenon to be responded to by Islamic boarding schools. This is because pesantren is an Islamic educational institution that teaches the Quran and Hadith, in which there are teachings to preserve nature and all its contents. In addition, pesantren produce graduates who master Islamic religious literacy properly and correctly so that they can preach nature conservation to the wider community. This research aims to provide literacy about Islamic education innovations that can be transformed from the concept of environment-based insight. In addition, to provide literacy regarding the criteria and implementation of eco-pesantren. The results of this study are the criteria and implementation of eco-friendly pesantren which include: 1) Environmentally friendly pesantren policy 2) Environmentally friendly Islamic curriculum 3) Nature taddabur activities 4) Supporting facilities and infrastructure to realize an environmentally friendly pesantren